2015
DOI: 10.1021/jacs.5b05971
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic or Dynamic Control on a Bifurcating Potential Energy Surface? An Experimental and DFT Study of Gold-Catalyzed Ring Expansion and Spirocyclization of 2-Propargyl-β-tetrahydrocarbolines

Abstract: In classical transition state theory, a transition state is connected to its reactant(s) and product(s). Recently, chemists found that reaction pathways may bifurcate after a transition state, leading to two or more sets of products. The product distribution for such a reaction containing a bifurcating potential energy surface (bPES) is usually determined by the shape of the bPES and dynamic factors. However, if the bPES leads to two intermediates (other than two products), which then undergo further transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 86 publications
0
61
0
1
Order By: Relevance
“…25,2529,32 In such a case, traditional transition state theory (TST), 33–36 where barriers to formation of two competing products are compared, cannot be used to predict experimental product distributions, because the two products share a TSS for their formation. PTSBs have been reported previously for some Au-catalyzed reactions, 3746 as well as a Rh-promoted C–H insertion reaction where the PTSB leads to both the direct insertion product and the product of a C–H activation/Cope rearrangement sequence. 4 Examination of structures along the IRC for the fragmentation reaction suggests that the reaction is asynchronous, with hydride transfer preceding C–O bond breaking (see ESI†).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…25,2529,32 In such a case, traditional transition state theory (TST), 33–36 where barriers to formation of two competing products are compared, cannot be used to predict experimental product distributions, because the two products share a TSS for their formation. PTSBs have been reported previously for some Au-catalyzed reactions, 3746 as well as a Rh-promoted C–H insertion reaction where the PTSB leads to both the direct insertion product and the product of a C–H activation/Cope rearrangement sequence. 4 Examination of structures along the IRC for the fragmentation reaction suggests that the reaction is asynchronous, with hydride transfer preceding C–O bond breaking (see ESI†).…”
Section: Resultsmentioning
confidence: 71%
“…2), secondary carbocations in terpene-forming cyclization/rearrangements, 3,26 π-complexes in Au-promoted cyclizations. 3746 One should not only interrogate reactions of interest for the presence of this scenario, but reactions with PTSBs also, in principle, can be designed by looking for (and rationally manipulating) putative intermediates expected to reside in extremely shallow energy wells that can be accessed from high energy TSSs. It is time to stop bumping into bifurcations and instead actively pursue both of these directions.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[17] Thus,both the metal catalyst and protecting group of the substrate are the key to achieve the desired cascade cyclization. Interestingly,this cascade cyclization was also extended to 3-substituted indole-tethered homopropargyl amides (5), and the desired aza-[3.2.1] skeletons 6a-h were formed in generally good yields,a ss ummarized in Table 4. Initial investigation of N-protecting groups of the amide moiety demonstrated that the reaction proceeded smoothly with different sulfonyl groups to furnish the desired aza-[3.2.1] skeletons 2a-d in 68-84 %yields (entries 1-4), and the Ts-protected homopropargyl amide 1a gave the best result (entry 1).…”
Section: Resultsmentioning
confidence: 98%
“…[2,3] In particular,there is alack of efficient synthetic methods for their enantioselective synthesis. [4,5] Meanwhile,s uch ac opper-catalyzed cyclization has been far less vigorously investigated, [6] and the internal nucleophiles here are limited to the more nucleophilic electron-rich amines,thus severely limiting their further synthetic applications as the N-protecting groups of the formed products are difficult for removal. [4,5] Meanwhile,s uch ac opper-catalyzed cyclization has been far less vigorously investigated, [6] and the internal nucleophiles here are limited to the more nucleophilic electron-rich amines,thus severely limiting their further synthetic applications as the N-protecting groups of the formed products are difficult for removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation